Pregnancy in Marfan Syndrome – Two Case Reports - Isidro Amaral, P (2016)
Marfan syndrome is a connective tissue disorder, autosomal dominant, which affects multiple organ systems, namely the cardiovascular, ocular and skeletal. Morbidity and mortality result primarily from aortic and cardiac complications including dilatation, dissection and rupture of the aorta. As a result, pregnancy in women with the Marfan syndrome has an increased risk. Main causes of complications are related with hemodynamic and hormonal modifications caused by pregnancy. The approach to pregnancy in patients with this syndrome is challenging and deserves special care. A multidisciplinary surveillance plan should be developed with support from cardiology, maternal fetal medicine, anesthesiology, genetics and pediatrics.